A Kascakova, Janka, and David Levente Palatinus, editors. J.R.R. Tolkien in Central Europe: Context, Directions, and the Legacy. Routledge, 2024. pp. ix + 188. ISBN 9781032525587 - AlSarhan, Taha (FOCUS: Papers in English Literary and Cultural Studies, 2024)
Janka Kascakova and David Levente Palatinus’ edited book J.R.R. Tolkien in Central Europe: Context, Directions, and the Legacy offers an in-depth examination of the development of Tolkien Studies in this region. The three chapters provide a substantial understanding of Hungarian, Slovakian, and Czech translations of Tolkien, and their reception in the latter decades of the twentieth century. Furthermore, the volume displays how the study of Tolkien might progress not only in Central Europe but also in the broader framework of the modern twenty-first-century evaluation of Tolkien’s significance as a foundational figure in the fantasy genre.